Chasing Traumatic Shadows: The Role of Memory in the Reincarnation of The Self In Chimamanda Ngozi Adichie’s Half of a Yellow Sun - Amina Saker (The Journal of Studies in Language, Culture and Society, 2019)
This paper endeavors to have a postcolonial reading of a third generation Nigerian trauma novel Half of a Yellow Sun; It aims at demonstrating how Chimamanda Nguzie Adichie’s  work could be read as a sophisticated postcolonial traumatic chronicle whereby the writer weaves national and personal traumatic historical memories with fiction. Basically, Adichie documents the 1967 to 1970 violent war inflicted upon the Igbo people in post-independent Nigeria. Using the doctrines of postcolonial and trauma theory and with emphasis on the role of traumatic memory in the reincarnation of the self, this paper argues that apparently because of the impact of the inherited Biafran crudest realities and memories on the writer, Adichie’s traumatic experiences as a child are assumed to commensurate with the portraits of her characters to some extent. In the same vein, this paper also sheds light on the trauma of the major characters like Olanna “the educated lady”, Ugwu “ the subordinate identified boy with his master”,and Richard “the writer of the book” taking into account the linguistic processes through which they could successfully struggle their traumatic memories. In the main, the practice of writing and narrating trauma is to be very significant to all of them as to adapt and work through these shadows and later reformalize their lost selfhood. Adichie’s traumatic retrospect and self reincarnation prospect is the main issue of this paper as an important process of unburdening, healing and reviving.